Cytosolic Delivery of Thiolated Neoantigen Nano‐Vaccine Combined with Immune Checkpoint Blockade to Boost Anti‐Cancer T Cell Immunity. Issue 6 (29th January 2021) - Zhang, Da; Lin, Ziguo; Wu, Ming; Cai, Zhixiong; Zheng, Youshi; He, Lei; Li, Zhenli; Zhou, Jie; Sun, Liqin; Chen, Geng; Zeng, Yongyi; Li, Juan; et al.
Abstract: Although tumor‐specific neoantigen‐based cancer vaccines hold tremendous potential, it still faces low cross‐presentation associated with severe degradation via endocytosis pathway. Herein, a thiolated nano‐vaccine allowing direct cytosolic delivery of neoantigen and Toll like receptor 9 agonist CpG‐ODN is developed. This approach is capable of bypassing the endo‐/lysosome degradation, increasing uptake and local concentration of neoantigen and CpG‐ODN to activate antigen‐presenting cells, significantly strengthening the anti‐cancer T‐cell immunity. In vivo immunization with thiolated nano‐vaccine enhanced the lymph organ homing and promoted the antigen presentation on dendritic cells, effectively inhibited tumor growth, and significantly prolonged the survival of H22‐bearing mice. Strikingly, further combination of the thiolated nano‐vaccine with anti‐programmed cell death protein‐1 antibody ( α PD‐1) could efficiently reverse immunosuppression and enhance response rate of tumors, which led to enhanced tumor elimination, complete prevention of tumor re‐challenge, and long‐term survival above 150 d. Collectively, a versatile methodology to design cancer vaccines for strengthening anti‐cancer T‐cell immunity in solid tumors is presented, which could be further remarkably enhanced by combining with immune checkpoint inhibitors. Abstract : A thiolated nano‐vaccine allowing direct cytosolic delivery of neoantigen and Toll like receptor 9 agonist CpG‐ODN is reported. This approach is capable of bypassing the endo‐/lysosome degradation, increasing uptake and local concentration of neoantigen and CpG‐ODN to activate antigen‐presenting cells, significantly strengthening anti‐cancer T‐cell immunity in solid tumors, which could be further remarkably enhanced by combining with immune checkpoint inhibitors.